2000
DOI: 10.1027//1016-9040.5.4.259
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Authoritarianism in the United States, England, and Hungary with Selected Nonrandom Samples

Abstract: It has been suggested that there is no such thing as a left-wing authoritarian, and that authoritarian attitudes do not correlate with authoritarian behaviors. Studies were done in the United States, England, and Hungary in order to obtain cross-cultural empirical data on these questions. An additional goal of the research was to use common measures across samples, which had not occurred in previous studies where comparisons were drawn. Left-wing authoritarians were not found in the United States or England, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…As in most studies on authoritarianism to date, students were chosen as the research population because of their relative accessibility. Studies dealing with ingroup-outgroup (e.g., racism, prejudice, authoritarianism) concepts have found that there are almost no differences between results based on student samples and general population samples (Pentony, Peterson, Phillips, Leong, Harper, Bakowski, Steward, and Gonzales, 2000;Sears, 1993). 4.…”
Section: Support For Democratic Values Measurementioning
confidence: 96%
“…As in most studies on authoritarianism to date, students were chosen as the research population because of their relative accessibility. Studies dealing with ingroup-outgroup (e.g., racism, prejudice, authoritarianism) concepts have found that there are almost no differences between results based on student samples and general population samples (Pentony, Peterson, Phillips, Leong, Harper, Bakowski, Steward, and Gonzales, 2000;Sears, 1993). 4.…”
Section: Support For Democratic Values Measurementioning
confidence: 96%
“…Looking for left-wing authoritarians in societies where the communist ideology has dominated for several decades has proven to be a fruitful approach. Multiple studies showed that in Hungary, Romania, Russia, Serbia and Yugoslavia authoritarianism correlates positively with support for: socialist ideology, socialist party preferences, positive feelings for communists, political left self-placement and communist principles (Enyedi and Todosijevi c, 2002;Krauss, 2002;McFarland et al, 1992McFarland et al, , 1993McFarland et al, , 1996Pentony et al, 2000;Todosijevi c, 2005Todosijevi c, , 2006Todosijevi c and Enyedi, 2008a, b).…”
Section: Shilsmentioning
confidence: 99%
“…Historically, many researchers have argued for the possibility of left‐wing authoritarianism (e.g., Eysenck, 1954; Mullen et al., 2003; Ray, 1983; Rokeach, 1960; Shils, 1954), and burgeoning evidence spanning multiple nations and three continents validates many of these conceptual arguments (Conway et al., 2018; Conway & McFarland, 2019; Costello et al., 2021; Conway et al., 2020b, 2021; Conway, Conway, et al., 2020; De Regt et al., 2011; Fasce & Avendaño, 2020; Federico et al., 2017; Malka et al., 2017; McFarland et al., 1992; McFarland et al., 1993; McFarland et al., 1996; Pentony et al., 2000; Todosijević, 2005; Todosijević & Enyedi, 2008; Van Hiel et al., 2006; Wronski et al., 2018). This evidence for LWA can be roughly grouped into two source types.…”
Section: Introductionmentioning
confidence: 99%